Effect of Al2O3 particle size on the microstructure, phase transformation and mechanical properties of hot pressed Al2O3-CA6-ZrO2/Ni multi-phase composites. Issue 10 (July 2020) - Zhang, Xi; Liang, Jinsheng; Li, Junguo; Li, Yuehua; Hao, Suju; Zeng, Yanan; Wang, Yitong
Abstract: Al2 O3 -CA6-ZrO2 /Ni multi-phase composites were fabricated by vacuum hot pressing sintering at 1650 °C under the pressure of 30 MPa for 30 min. The microstructural evolution rule of the composites was investigated as a function of Al2 O3 particle size. Upon increasing the Al2 O3 particle size to 30 μm, the generated CA6 underwent a transformation from unfixed type to a plate-like pattern and to a combined CA6-Al2 O3 matrix, whereas the fracture mode of m-ZrO2 changed from an intergranular fracture to an intergranular and transgranular mixed type due to the improved interface binding energy. Additionally, satisfactory mechanical properties of the composites were achieved when the Al2 O3 particle size was 30 μm. Under the synergistic effect of different strengthening and reinforcing phases, the inhomogeneous distribution caused by poor wettability between Al2 O3 and Ni was effectively solved by the distributions of "intercrystalline type" and "intracrystalline type" for the Ni phase. The mechanisms of the microstructural evolution, phase transformation and improved mechanical properties are discussed in detail.